2021
DOI: 10.1590/01047760202127012886
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting some properties on surface of thermowood material applied with water-based varnishes modifed with nanoparticles

Abstract: Background:The aim of this study is to determine the surface roughness and adhesion strength of water-based varnishes modified with nanoparticles of zinc oxide (ZnO) and hollow ceramic spherical (HCS) against accelerated UV aging effect in some ThermoWood materials. For this purpose, American ash (Fraxinus americana) and scotch pine (Pinus sylvestris Lipsky) wood were heat treated at a temperature of 190 °C for 1.5 hours and 212 °C for 2 hours. The heat-treated samples were applied with two-component water-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the literature, it has been reported that there are changes in the varnish layers after accelerated weathering in different wood species that have been applied to various varnishes (water-based, UV system, acrylic, etc.) (Çakıcıer 2007;Ayata 2019;Karamanoğlu 2020;Ayata et al 2021a,b).…”
Section: Results For Total Color Differencesmentioning
confidence: 99%
“…In the literature, it has been reported that there are changes in the varnish layers after accelerated weathering in different wood species that have been applied to various varnishes (water-based, UV system, acrylic, etc.) (Çakıcıer 2007;Ayata 2019;Karamanoğlu 2020;Ayata et al 2021a,b).…”
Section: Results For Total Color Differencesmentioning
confidence: 99%